STUDIES ON FLORAL DIVERSITY AND ETHNOBOTANICAL ASPECTS OF THE DISTRICT OF PATNA BIHAR - MADHVI SUMAN (International Journal of Multidisciplinary Research and Studies, 2020)
Plants are necessary for human life, providing important resources such as food, clothing, fuel, medicine, wood, and crucial ecological functions. These essential resources include food, clothing, fuel, medicine, and wood. It is impossible for humans to survive without plants. The use of natural and medicinal treatments derived from wild plants is something that each member of the local community does as part of their habits. According to the World Health Organization, about 80% of the world's poor countries, including India, still rely on traditional medicines for primary health care. This includes the treatment of infectious diseases. People continue to find new uses for various herbal products over time. If we were to scan the annals of human history, we would see that man, in one way or another, has relied on plant products to meet his basic needs such as food, shelter, and clothing since the dawn of mankind on this planet. If we were to look back in the annals of human history, we would see that human beings have relied on plant products to meet their basic needs since the dawn of humanity on this planet. It is very important for the growth of civilization in a given place that there is a close connection between man and plants.